2021
DOI: 10.1101/2021.06.14.21258875
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mild Adverse Events of Sputnik V Vaccine Extracted from Russian Language Telegram Posts via BERT Deep Learning Model

Abstract: Background: There is a limited amount of data on the COVID-19 vector vaccine Gam-COVID-Vac (Sputnik V) safety profile. Previous infodemiology studies showed that social media discourse could be analyzed to assess the most concerning adverse events (AE) caused by drugs. Objective: We aimed to investigate mild AEs of Sputnik V based on a participatory trial conducted on Telegram in the Russian language. We compared AEs extracted from Telegram with other limited databases on Sputnik V and other COVID-19 vaccines.… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 43 publications
(45 reference statements)
0
4
0
Order By: Relevance
“…Previous studies showed that the most common side effects of the Sputnik vaccine were injection site pain followed by fever, fatigue, headache, lethargy, and muscle and joint pain. 32 , 33 Our results revealed that the most common complication of Sputnik was muscle pain followed by fever, fatigue, chills, topical reaction, cold-like symptoms, and dizziness or headache. The most common side effects of the Covaxin vaccine were fever, topical reaction, fatigue, muscle pain, chills, cold-like symptoms, and dizziness or headache.…”
Section: Discussionmentioning
confidence: 66%
“…Previous studies showed that the most common side effects of the Sputnik vaccine were injection site pain followed by fever, fatigue, headache, lethargy, and muscle and joint pain. 32 , 33 Our results revealed that the most common complication of Sputnik was muscle pain followed by fever, fatigue, chills, topical reaction, cold-like symptoms, and dizziness or headache. The most common side effects of the Covaxin vaccine were fever, topical reaction, fatigue, muscle pain, chills, cold-like symptoms, and dizziness or headache.…”
Section: Discussionmentioning
confidence: 66%
“…As mentioned earlier (Figure 2), in our study, 12 complications (e.g., topical reactions, fatigue, and muscle pain) showed a significantly higher occurrence rate in women than in men. The results of previous studies have reported this finding on the effects of different vaccines, including AstraZeneca and Sputnik (16,18,19). However, the results of some studies showed no significant difference between men and women (15,20).…”
Section: Discussionmentioning
confidence: 79%
“…Occurrences of adverse events were higher in females and in the age groups below 55 years. A recent infodemiology study by Jarynowski et al [202] claims Sputnik V to cause mild to moderate adverse effects in females compared to males and increasing in number with increaseing age (0.05/year, p<0.001). Reported adverse events were in line with other vector vaccines including fever, pain, fatigue, and headache.…”
Section: Untoward Effectsmentioning
confidence: 99%